Jose E. Cuisia professorial chair in business ethics lecture of Dr. Benito L. Teehankee - Teehankee, Benito L. (Animo Repository, 2021)
De La Salle University Ramon V. del Rosario College of Business Management and Organization Department Invited the academic community to the Professorial Chair Lecture of Benito L. Teehankee, DBA, holder of the Jose E. Cuisia Sr. Professorial Chair in Business Ethics "Commonalities of action research and Catholic Social Teachings in promoting social change for justice and emancipation: The case of the Covenant for Shared Prosperity